Rhetorical Strategy and Linguistics Features in E-Petition Through Change.org - Fatkhiyati, Nurrahma Restia; Suharno, Suharno (Bina Nusantara University, 2019)
The research explored what types and how rhetorical strategy correlated with the linguistics features in e-petitions throughÂ Change.org entitled â€œKPK dalam Bahayaâ€. The data were e-petitions collected through Change.org. The analysis wasÂ holistically descriptive and included in qualitative research. The approach used critical discourse analysis by FaircloughÂ that was using Faircloughâ€™s three-dimensional framework and the strategy of rhetoric by Aristotle. Those theories helpedÂ the researcher to find out how the rhetorical strategy and the linguistics features created persuasive meaning. The findingsÂ indicate that euphemism, metaphor, connectives, logical connectors, rhetorical questions, and modality support the rhetoricÂ strategy constructing the meaning beyond the words. Through one of the rhetoric strategies, pathos persuades the readersÂ to agree to the argument and sign the e-petitions. Due to the emotional appeals, all of these language instruments help theÂ rhetoric to provoke the readers significantly.